Influence of alloying elements on cellular response and in-vitro corrosion behavior of titanium-molybdenum-chromium alloys for implant materials. Issue 4 (October 2020) - Mat-Baharin, Nor Haliza; Razali, Masfueh; Mohd-Said, Shahida; Syarif, Junaidi; Muchtar, Andanastuti
Abstract: Purpose: Not all elements with β-stabilizing properties in titanium alloys are suitable for biomaterial applications, because corrosion and wear processes release the alloying elements to the surrounding tissue. Chromium and molybdenum were selected as the alloying element in this work as to find balance between the strength and modulus of elasticity of β-titanium alloys. This study aimed to investigate the effect of Titanium-10Molybdenum-10Chromium (Ti-10Mo-10Cr), Titanium-10Chromium (Ti-10Cr) and Titanium-10Molybdenum (Ti-10Mo) on the elemental leachability in tissue culture environment and their effect on the viability of human gingival fibroblasts (HGFs). Methods: Each alloy was immersed in growth medium for 0–21 days, and the elution was analyzed to detect the released metals. The elution was further used as the treatment medium and exposed to seeded HGFs overnight. The HGFs were also cultured directly to the titanium alloy for 1, 3 and 7 days. Cell viability was then determined. Results: Six metal elements were detected in the immersion of titanium alloys. Among these elements, molybdenum released from Ti-10Mo-10Cr had the highest concentration throughout the immersion period. Significant difference in the viability of fibroblast cells treated with growth medium containing metals and with direct exposure technique was not observed. The duration of immersion did not significantly affect cell viability. Nevertheless, cell viability was significantly affected after 1 and 7 days of exposure, when the cells were grown directly onto the alloy surfaces. Conclusions: Within the limitation of this study, the newly developed β-titanium alloys are non-cytotoxic to human gingival fibroblasts.